Regional reduction in cortical blood flow among cognitively impaired adults with relapsing-remitting multiple sclerosis patients - Hojjat, Seyed-Parsa (Mult Scler, 2016)
PURPOSE: Detection of cortical abnormalities in relapsing-remitting multiple sclerosis (RRMS) remains elusive. Structural MRI measures of cortical integrity are limited, although functional techniques such as pseudocontinuous Arterial Spin Labeling (pCASL) show promise as a surrogate marker of disease severity. We sought to determine the utility of pCASL to assess cortical cerebral blood flow (CBF) in RRMS patients with (RRMS-I) and without (RRMS-NI) cognitive impairment. METHODS: 19 age-matched healthy controls and 39 RRMS patients were prospectively recruited. Cognition was assessed using the MACFIMS battery. Cortical CBF was compared between groups using a mass univariate voxel-based morphometric analysis accounting for demographic and structural variable covariates. RESULTS: Cognitive impairment was present in 51.3% of patients. Significant CBF reduction was present in the RRMS-I compared to other groups in left frontal and right superior frontal cortex. Compared to healthy controls, RRMS-I displayed reduced CBF in the frontal, limbic, parietal and temporal cortex and putamen/thalamus. RRMS-I demonstrated reduced left superior frontal lobe cortical CBF compared to RRMS-NI. No significant cortical CBF differences were present between healthy controls and RRMS-NI. CONCLUSION: Significant cortical CBF reduction occurs in RRMS-I compared to healthy controls and RRMS-NI in anatomically significant regions after controlling for structural and demographic differences.